CHARMM‐GUI Martini Maker for modeling and simulation of complex bacterial membranes with lipopolysaccharides. Issue 27 (3rd August 2017) - Hsu, Pin‐Chia; Bruininks, Bart M. H.; Jefferies, Damien; Cesar Telles de Souza, Paulo; Lee, Jumin; Patel, Dhilon S.; Marrink, Siewert J.; Qi, Yifei; Khalid, Syma; Im, Wonpil
Abstract : A complex cell envelope, composed of a mixture of lipid types including lipopolysaccharides, protects bacteria from the external environment. Clearly, the proteins embedded within the various components of the cell envelope have an intricate relationship with their local environment. Therefore, to obtain meaningful results, molecular simulations need to mimic as far as possible this chemically heterogeneous system. However, setting up such systems for computational studies is far from trivial, and consequently the vast majority of simulations of outer membrane proteins still rely on oversimplified phospholipid membrane models. This work presents an update of CHARMM‐GUI Martini Maker for coarse‐grained modeling and simulation of complex bacterial membranes with lipopolysaccharides. The qualities of the outer membrane systems generated by Martini Maker are validated by simulating them in bilayer, vesicle, nanodisc, and micelle environments (with and without outer membrane proteins) using the Martini force field. We expect this new feature in Martini Maker to be a useful tool for modeling large, complicated bacterial outer membrane systems in a user‐friendly manner. © 2017 Wiley Periodicals, Inc. Abstract : An outer membrane vesicle generated by CHARMM‐GUI Martini Maker with lipopolysaccharides in the outer leaflet and phospholipids in the inner leaflet.